2021
DOI: 10.3389/fagro.2021.609536
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Agroforestry Yield Buffering Potential Under Climate Change in the Smallholder Maize Farming Systems of Ethiopia

Abstract: Agroforestry is a promising adaptation measure for climate change, especially for low external inputs smallholder maize farming systems. However, due to its long-term nature and heterogeneity across farms and landscapes, it is difficult to quantitatively evaluate its contribution in building the resilience of farming systems to climate change over large areas. In this study, we developed an approach to simulate and emulate the shading, micro-climate regulation and biomass effects of multi-purpose trees agrofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…Based on statistical metrics, the evaluation of the performance showed that fourteen GCMs (Table 10) have sufficient performance when evaluated with observations from Harare Metropolitan gauging stations (d > 0.7, r > 0.7 and R 2 > 0.5), with the exception of MRI-CGCM3, observed to have the lowest determination coefficient of 0.47. This may suggest that the general circulation model could have other specific years that were not properly simulated [63]; however, the analysis shows that most GCMs displayed good simulation. Above all, the GCMs have an rRMSE below 20%, which is reasonably acceptable [116,117,129].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Based on statistical metrics, the evaluation of the performance showed that fourteen GCMs (Table 10) have sufficient performance when evaluated with observations from Harare Metropolitan gauging stations (d > 0.7, r > 0.7 and R 2 > 0.5), with the exception of MRI-CGCM3, observed to have the lowest determination coefficient of 0.47. This may suggest that the general circulation model could have other specific years that were not properly simulated [63]; however, the analysis shows that most GCMs displayed good simulation. Above all, the GCMs have an rRMSE below 20%, which is reasonably acceptable [116,117,129].…”
Section: Discussionmentioning
confidence: 90%
“…However, uncertainties in GCMs primarily exist on biases of raw outputs, resulting in either over or underestimation of climate variables due to erroneous assumptions in the model's development [60,61]. As such, many studies have embarked on the use of multi-modelling techniques to minimize the uncertainty of future predictions in order to obtain plausible future projections [62][63][64][65][66].…”
Section: Climate Change Emission Scenariosmentioning
confidence: 99%
See 3 more Smart Citations